Study on the Effect of PDA-PLGA Scaffold Loaded With Islet Cells for Skeletal Muscle Transplantation in the Treatment of Diabetes - Zhang, Meishuang; Du, Hongwei; Guan, Yueqi; Liu, Jingyue; Wang, Sushan; Li, Haoran; Zhang, Wenyou; Han, Hao; Zhang, Ming; Chen, Li (Frontiers in Bioengineering and Biotechnology, 2022)
At present, islet cells transplantation was limited by the way in which islet cells are implanted into the body, their ability to adapt to the microenvironment and the maintenance time for relieving diabetic symptoms. In order to solve this problem, we made PDA-PLGA scaffold loaded with islet cells and used it for skeletal muscle transplantation to investigate its therapeutic effect in the treatment of diabetes. The PLGA scaffold was prepared by the electrospinning method, and modified by polydopamine coating. A rat diabetic model was established to evaluate the efficacy of PDA-PLGA scaffold loaded with RINm5f islet cells through skeletal muscle transplantation. The results showed that the PDA-PLGA scaffold has good biosafety performance. At the same time, transplantation of the stent to the skeletal muscle site had little effect on the serum biochemical indicators of rats, which was conducive to angiogenesis. The PDA-PLGA scaffold had no effect on the secretory function of pancreatic islet cells. The PDA-PLGA scaffold carrying RINm5f cells was transplanted into the skeletal muscle of type I diabetic rats. One week after the transplantation of the PDA-PLGA cell scaffold complex, the blood glucose of the treatment group was significantly lower than that of the model group (p<0.001) and lasted for approximately 3 weeks, which further indicated the skeletal muscle transplantation site was a new choice for islet cell transplantation in the future.